2012
DOI: 10.11609/jott.o3074.2685-92
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and community structure of dung beetles (Coleoptera: Scarabaeinae) associated with semi-urban fragmented agricultural land in the Malabar coast in southern India

Abstract: An evaluation of the diversity and community structure of dung beetles associated with semiurban agricultural land in the Malabar coast of southern India revealed that urbanization has led to decreased diversity compared to regional forests, and has affected the community status of dung beetles. However, contrary to expectations, species richness was observed to be equivalent to rural agricultural fields in the region. Low abundance of prominent agricultural habitat species indicates that the study area has ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 35 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…Their tunneling behavior is associated with their horn (Emlen and Phillips 2006). Tunnelers were mostly abundant in forest habitats while dwellers in open agricultural habitats (Hanski and Cambefort 1991;Venugopal et al 2012). The small tunnelers have more diverse food habits (coprophagous, necrophagous and generalist) and large niche forest habitat, so these dung beetles can be a majority dung beetles in Oriental region, especially in South-east Asian forests (Hanski and Cambefort 1991).…”
Section: Dominant Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their tunneling behavior is associated with their horn (Emlen and Phillips 2006). Tunnelers were mostly abundant in forest habitats while dwellers in open agricultural habitats (Hanski and Cambefort 1991;Venugopal et al 2012). The small tunnelers have more diverse food habits (coprophagous, necrophagous and generalist) and large niche forest habitat, so these dung beetles can be a majority dung beetles in Oriental region, especially in South-east Asian forests (Hanski and Cambefort 1991).…”
Section: Dominant Speciesmentioning
confidence: 99%
“…In this study, the dung beetle diversity showed a marked seasonality in the study region where the high abundance and species richness presented in dry season (August 2017 and 2018). In India, the study of Venugopal et al (2012) in open agricultural field and Latha (2019) in forests showed the different results where the highest abundance of dung beetles was found during rainy period so the soil is softer to support the abundance of dung beetles. Andresen (2005) and Hernandez et al (2014) also showed that dung beetles highly captured during rainy period in Mexican dry forests and Restinga forest, respectively.…”
mentioning
confidence: 99%
“…Life history (Klemperer, 1983): Adults of this diurnal scarab are active throughout the year (Venugopal et al, 2012), and may show some preference for forested habitat. Females create a brood chamber within a dung pat and create brood balls from the surrounding…”
Section: Plant Host(s)mentioning
confidence: 99%
“…DISCUSSION Low abundance, species richness and diversity recorded during the northeast monsoon season in the agriculture habitat in Nelliampathi is in contrast to results observed in the forest (Latha, 2019;Vinod, 2009) and agriculture habitat (Venugopal et al, 2012;Vinod, 2009) of the South Western Ghats region, where high abundance, species richness and diversity was observed in the northeast monsoon season. Dung beetle seasonality studies done in other parts of the world also show that activity is greatest during moist and minimal during dry periods and the abundance of scarab beetles increases strongly after heavy rainfall (Walter, 1985;Doube et al, 1991;Hanski and Krikken, 1991;Andresen, 2005;Batista et al, 2016).…”
Section: IVmentioning
confidence: 54%